Art as power of self, the lecture-performance and the epistemologist-actor (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
In recent years, the lecture-performance has emerged as a crucial format in the practice of contemporary theater. From a genealogical process that announces a possible identification and recognition coverage, the authors explore in recent theatrical production elements and distinctiveness that compose this hybrid theatrical practice, which absorb spatial and material elements of both the academic lecture as well the artistic performance and from that, we have the presence of a new type of the actor: the epistemologist-actor.
Keywords: Lecture-performance; Contemporary theater; Queer theory; Decoloniality; Epistemologist-actor